One-pot Synthesis of 5-Unsubstituted 3, 4-Dihydropyrimidin-2(1H)-ones from Aldehydes, Ketones, and Urea under Solvent-free Conditions. (26th May 2016) - Song, Zhiguo; Sun, Xiaohu; Yang, Xibao
Abstract : Various 5-unsubstituted 3, 4-dihydropyrimidin-2(1 H )-ones were synthesized efficiently by a one-pot three-component condensation of aromatic aldehydes, aromatic ketones, and urea using SnCl2 ·2H2 O as a catalyst under solvent-free conditions. All products were identified by IR, NMR, MS, and elemental analysis. The novel method offers several advantages such as excellent yields (81–95%), short reaction time (5–16 min), broader substrate scope, and environmentally friendly conditions.